The vulnerability of Indo-Pacific mangrove forests to sea-level rise - Lovelock, Catherine E.; Cahoon, Donald R.; Friess, Daniel A.; Guntenspergen, Glenn R.; Krauss, Ken W.; Reef, Ruth; Rogers, Kerrylee; Saunders, Megan L.; Sidik, Frida; Swales, Andrew; Saintilan, Neil; Thuyen, Le Xuan; et al. (Nature (London), 2015)
Assessment of mangrove forest surface elevation changes across the Indo-Pacific coastal region finds that almost 70 per cent of the sites studied do not have enough sediment availability to offset predicted sea-level rise; modelling indicates that such sites could be submerged as early as 2070. Mangrove forests on the verge Intertidal mangrove forests provide a wide range of ecosystem services, including coastal protection and carbon storage. Their survival can be threatened by sea-level rise, but the forests can avoid inundation if there is sufficient sediment supply to allow them to maintain soil elevations suitable for plant growth. This study analyses recent trends in mangrove surface elevation changes across the Indo-Pacific region and finds that sediment availability is important to maintaining rates of soil-surface elevation gain that matched or exceeded that of sea-level rise, but that 69% of the forest study sites had rates of soil-surface elevation gain less than that of sea-level rise. Numerical modelling based on the field data suggests that mangrove forests at sites with low tidal range and low sediment supply could be submerged as early as 2070. Sea-level rise can threaten the long-term sustainability of coastal communities and valuable ecosystems such as coral reefs, salt marshes and mangroves 1 , 2 . Mangrove forests have the capacity to keep pace with sea-level rise and to avoid inundation through vertical accretion of sediments, which allows them to maintain wetland soil elevations suitable for plant growth 3 . The Indo-Pacific region holds most of the world’s mangrove forests 4 , but sediment delivery in this region is declining, owing to anthropogenic activities such as damming of rivers 5 . This decline is of particular concern because the Indo-Pacific region is expected to have variable, but high, rates of future sea-level rise 6 , 7 . Here we analyse recent trends in mangrove surface elevation changes across the Indo-Pacific region using data from a network of surface elevation table instruments 8 , 9 , 10 . We find that sediment availability can enable mangrove forests to maintain rates of soil-surface elevation gain that match or exceed that of sea-level rise, but for 69 per cent of our study sites the current rate of sea-level rise exceeded the soil surface elevation gain. We also present a model based on our field data, which suggests that mangrove forests at sites with low tidal range and low sediment supply could be submerged as early as 2070.